2019
DOI: 10.18355/xl.2019.12.03.14
|View full text |Cite
|
Sign up to set email alerts
|

Kierkegaard on the reconciliation of conscience

Abstract: Many authors have interpreted Kierkegaard's thought as a dialectical tragedy whose inevitable outcome is the sinking of the self in the despair of an unreconcilable consciousness. It cannot be denied that there are in Kierkegaard certain intentional excesses that may seem to support this interpretation. However, there is also in his thought a totalizing intuition and a harmonic vision of human existence that unify the dialectical struggle of the self. The deepest intention of free becoming is personal identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to Bergmann, Overmyer & Wilie 4 , a flipped classroom is replacing direct instruction with videos and encouraging students to focus on important learning activities with their teachers inside the classroom. Additionally, the flipped classroom allows the teacher to be a facilitator and also increase interaction and "personalized contact time" between teachers and students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bergmann, Overmyer & Wilie 4 , a flipped classroom is replacing direct instruction with videos and encouraging students to focus on important learning activities with their teachers inside the classroom. Additionally, the flipped classroom allows the teacher to be a facilitator and also increase interaction and "personalized contact time" between teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by McLaughlin and Rhoney (2015) [25], they found that the teachers 4 who used the flipped classroom approach developed higher awareness of teaching strategies. In addition, Kong (2014) [21] asserted that teachers who used the flipped approach improved their resources, experienced reflective discussions and shared their instructional practices.…”
Section: Introductionmentioning
confidence: 99%
“…Identity development supports the building of the social skills of individuals. Sensitivity to the environment is part of a person's ability to empathise and observe the consequences of socio-pathological phenomena in society [34,35]. Next in our study, the youngest children and adolescents were perceived by the participants as the most vulnerable groups during the pandemic.…”
Section: Discussionmentioning
confidence: 85%
“…In this way, it is in Christianity (Christendommen) (not in "bible-bashing" or false Christianity (Christenheden), worldly and lacking in existential and spiritual rigour, as Kierkegaard would say) that love is conjoined and revealed in its most sublime and authentic sense (Binetti & Pavlikova, 2019;. However, taking into account that it is not a selfish love nor one that looks to itself, but on the contrary, it is a love of the Other, it is a way of getting away from oneself and loving to the utmost.…”
Section: Kierkegaard: Ethics and The Individualmentioning
confidence: 99%